Impact of Covid-19 Pandemic On Psychological Behavior of Dental Health Care Workers in Peshawar: Impact of Covid-19 Pandemic on Dental Health Care Workers - Yousaf, Muhammad; Khan, Ariffullah; Shah, Farah; Kiramat, Sana; Ud Din, Ihtesham; Khan, Farzeen (Pakistan Journal of Health Sciences, 2022)
During the hard time of Covid, front line health care workers were directly involved in one way or the other to treat the patients or perform duties in Covid-wards. They were at great risk of catching the infection as well as be affected by the psychological disorders. Objective: To determine the effects of Covid pandemic on the psychological health of dental health care professionals in Peshawar. Methods: A total of 384 participants both Dentists and Dental paramedical staff and technicians were included in the study. The participants were classified as non-infected and Covid recovered participants. Two validated questionnaires (PHQ-9 scale, Scale for COVID-19 related psychological distress in healthy Dental health care workers) were used for these two types of participants respectively to assess the level of mental distress. The distress scores were analyzed and compared among various groups. Results: The results showed that non infected DHCWs generally had mild (48.98%) to moderate (31.43%) psychological distress as a result of the Covid situation. While Covid recovered DCHWs had minimal (30.86%) and moderate depression (30.07%) The particularly vulnerable groups showing more psychological distress were non-infected female DHCWs and non-infected DHCWs working at Lady Reading hospital Peshawar. Conclusion: The Covid-19 pandemic affected the mental health of DHCWs in a negative way, and most of the DHCWs had mild to moderate severity of distress or depression.